Reading "The Clash of Civilizations" after 25 years from its publication. Book Review: Orsi, D. (CORD). (2018) - Carranco Paredes, Santiago (2019)
The present text aims to recapitulate the main ideas proposed in the text the “Clash of Civilizations 25 Years On: A Multidisciplinary Appraisal” edited by Davide Orsi. At the same time, it presents an account of the thesis proposed 25 years ago by Samuel P. Huntington about the clash of civilizations and the way in which such thoughts have influence in the current political affairs. The aim of the book is to present the concepts of the Clash of Civilizations  and its derivations in order to demonstrate the ways in which they have developed, evolved or transformed to explain and understand contemporary global politics.